Papillary thyroid carcinoma of thyroglossal duct cyst; a case report and review of the literature - Shelke, VN; Raut, WK (Journal of Pathology of Nepal, 2012)
Thyroglossal duct remnants are the most common midline neck swellings, but malignancy arising in them is a rare finding. Among the carcinomas arising in the thyroglossal duct cyst, papillary thyroid carcinoma is the commonest. Most of the cases of papillary thyroid carcinoma of thyroglossal duct cyst are asymptomatic and clinically diagnosed as thyroglossal duct cyst. It may remain undetected on fine needle aspiration cytology and ultrasonography; therefore diagnosis is established only after pathologic evaluation of biopsy. Hence careful histopathological examination of the excised specimen with high level of suspicion is mandatory in these cases. We are report a case of papillary thyroid carcinoma of thyroglossal duct cyst in a 30-year-old female. Journal of Pathology of Nepal (2012) Vol. 2, 328-330 DOI: http://dx.doi.org/10.3126/jpn.v2i4.6889